ANALISIS PRAANGGAPAN DALAM IKLAN BCA REALITA RAMADAN DARI MATA CHRISTINE HAKIM #TIBATIBATENANG DI YOUTUBE DI YOUTUBE - Aisyah Salma Rasyidah; Muhammad Sulton Maulana; Muhammad Rohmadi (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to describe the forms of presuppositions and to describe the types of presuppositions based on George Yule's theory in BCA advertisements on the reality of Ramadan from the eyes of Christine Hakim #tibatibatenang on YouTube. This research is a qualitative descriptive research using document analysis method. The data sources used are words, phrases, and sentences that have presupposition indicators in BCA advertisements on the reality of Ramadan from the eyes of Christine Hakim #tibatibatenang on YouTube. The data was analyzed through 5 stages, namely identifying the data, classifying the data, describing the data, concluding the data, and presenting the results of data analysis. The researcher concluded that the results of this study contained 12 research data that had been collected, there were 4 existential presuppositions, 3 inactive presuppositions, 1 lexical presupposition, 2 non-factive presuppositions, 1 counterfactual presupposition, and 1 structural presupposition.